SUBJECT AND FIGURATIVE CONTENT OF PROVERBS AND SAYINGS, VERBALIZED EMOTIONAL CONCEPT "FEAR" IN ENGLISH AND KAZAKH LINGOCULTURES - Ismagulova, A.E.; Kairat, G. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
Proverbs and sayings are created by people throughout the centuries, therefore their research (as well as research of phraseological units) represents a certain contribution to concept research from the point of view of its diachronic formation. In proverbial – saying fund of language information is saved up and clearly seen specifics of representation and understanding of fear. In article the comparative analysis is given to the subject- figurative content of proverbs and sayings, verbalized an emotional concept "fear" in English and Kazakh lingocultures.
Keywords: proverbs and sayings; paroemia; concept; emotion; lingoculture